Performance of cementitious mortars containing hydrogel–nanoclay hybrid nanocomposite - Filho, Adhemar Watanuki; de Moura, Marcia Regina [UNESP]; Aouada, Fauze Ahmad [UNESP] (Springer Nature, 2024)
Cement-based composites comprise a binder matrix with or without aggregates. Hydration of cement is an exothermic reaction that releases considerable quantities of heat, causes drying shrinkage. Hydrogels can help mitigate such cracking as their hydrophilic characteristics and 3D crosslinked structure enables them to absorb and directly release water into the cement matrix over time. This study aims to synthesize and analyze the effect of adding hybrid nanocomposite hydrogels with different concentrations (0, 10, and 20% w/v) of Cloisite-Na+ nanoclay in their fresh and hardened cement mortar states. The hydrogels were synthesized via free radical polymerization, and four cementitious mortar samples (M, M0, M10, and M20). The results demonstrated that the density of all the mortars in the fresh state was ~2.16 ± 0.01 g.cm−3, but a decreasing trend was observed that could attributed to the increase of air incorporation into the mortar. At 28 days, the results indicated that the hydrogel with 20% Cloisite-Na+ was the most efficient, causing a reduction of ~4.4% in water absorption by the mortar. For all, three curing conditions considered, all mortars demonstrated considerable shrinkage over time. However, the controlled curing indicated that M20 mortars demonstrated 31% less shrinkage compared to the control sample. The scientific relevance of incorporating hydrogels into cement mortars lies in their ability to effectively address critical issues related to shrinkage-induced cracking and deterioration. Moreover, the use of hydrogels aligns with sustainable construction practices by reducing the need for additional water and minimizing the environmental impact associated with cement materials production. Graphical Abstract: (Figure presented.)
Keywords: Absorbent polymer; Civil construction; Hydrogel; Nanocomposite; Portland cement